2013
DOI: 10.1016/j.bcp.2013.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Quinone compounds regulate the level of ROS production by the NADPH oxidase Nox4

Abstract: NADPH oxidase Nox4 is expressed in a wide range of tissues and plays a role in cellular signaling by providing reactive oxygen species (ROS) as intracellular messengers. Nox4 oxidase activity is thought to be constitutive and regulated at the transcriptional level; however, we challenge this point of view and suggest that specific quinone derivatives could modulate this activity. In fact, we demonstrated a significant stimulation of Nox4 activity by 4 quinone derivatives (AA-861, tBuBHQ, tBuBQ, and duroquinone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 50 publications
(69 reference statements)
2
21
0
3
Order By: Relevance
“…Since PAHs leads to reticulum stress (Laing et al 2010), the expression of NOX4 mRNA could be induced (Bedard and Krause 2007), contributing to the O 2 − production. Actually, recent studies showed that quinone compounds, like the intermediates of PAHs metabolism, regulate the O 2 − production by NOX4 (Nguyen et al 2013). …”
Section: Discussionmentioning
confidence: 98%
“…Since PAHs leads to reticulum stress (Laing et al 2010), the expression of NOX4 mRNA could be induced (Bedard and Krause 2007), contributing to the O 2 − production. Actually, recent studies showed that quinone compounds, like the intermediates of PAHs metabolism, regulate the O 2 − production by NOX4 (Nguyen et al 2013). …”
Section: Discussionmentioning
confidence: 98%
“…Oxidative stresses caused by ROS can induce rapid depolarization of bacteria cells. In the redox process of the quinonoid compound, superoxide anions are the most likely chemical species to be formed in the oxide stage . To investigate this possibility, we monitored superoxide production using the NBT assay (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…NADPH oxidase exists in a wide range of tissues and plays a role in cellular signaling by generating ROS [27]. Another study indicated some specific quinine derivatives could modulate the activity of NADPH oxidase [28].…”
Section: Discussionmentioning
confidence: 99%